Contested Communities : Class, Gender, and Politics in Chile's El Teniente Copper Mine, 1904-1951 - Klubock, Thomas Miller (Book collections on Project MUSE., 1998)
In Contested Communities Thomas Miller Klubock analyzes the experiences of the El Teniente copper miners during the first fifty years of the twentieth century. Describing the everyday life and culture of the mining community, its impact on Chilean politics and national events, and the sense of self and identity working-class men and women developed in the foreign-owned enclave, Klubock provides important insights into the cultural and social history of Chile.